Bilateral ovarian maldescent: Unusual cause of infertility – A case report and literature review. Issue 8 (20th April 2016) - Garg, D.; Grazi, R.; Kankanala, N.; Melzer‐Ross, K.
Abstract: Infertility due to ovarian maldescent is extremely rare and diagnosis can be challenging in the absence of uterine anomalies. We present a case of infertility due to bilateral ovarian maldescent with normal uterine anatomy who conceived after in vitro fertilization and did not require removal of the ovaries. A 19‐year‐old woman presented with primary infertility. After three failed cycles of ovulation induction/intrauterine insemination and one failed cycle of fresh embryo transfer, the patient underwent laparoscopy, which showed bilateral ovaries above the pelvic brim. The patient conceived after second in vitro fertilization and delivered at 34 weeks. Accurate diagnosis of ovarian maldescent in a patient of unexplained infertility and normal uterus is crucial for successful follicular aspiration and infertility treatment. It is important to counsel patients about the benign nature of this rare entity and future fertility.